1999
DOI: 10.1590/s1516-35981999000200023
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho produtivo de animais de quatro raças zebuínas, abatidos em três estádios de maturidade: 2. características da carcaça

Abstract: RESUMO -Com a finalidade de estudar as características da carcaça, nove animais Gir, nove Guzerá, nove Nelore e nove Mocho-Tabapuã não-castrados, com idade média de 24 meses e pesos vivos médios iniciais de 357,6; 362,0; 368,6; e 376,4 kg, respectivamente, foram usados neste estudo. Em cada raça, os animais foram distribuídos aleatoriamente em baias individuais, recebendo ração contendo 50% de concentrado na matéria seca à vontade e divididos em três pesos de abate (categorias 405, 450 e 500 kg PV). No abate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1
32

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 0 publications
1
10
1
32
Order By: Relevance
“…Rib eye area increased linearly as slaughter weight increased, which was similar to the results reported in the literature, in which increase in body weight at slaughter resulted in greater REA, both in late breeds, like Charolais (Restle et al, 1997); early breeds, like Aberdeen Angus (Costa et al, 2002b); crossings between various breeds (Cruz et al, 2004b); and Zebu breeds, like Gyr, Guzerat, Tabapuã and Nellore (Jorge et al, 1999). The rib eye area expressed in 100 kg cold carcass decreased with increase in body weight, agreeing with the results observed in the literature, demonstrating linear decrease from 27 to 24 and from 26.2 to 23.2 cm 2 /100 kg carcass, with increase in slaughter weight from 550 to 700, in crossbred Blonde D'Aquitaine × Charolais (Patterson et al, 1994) and from 440 to 507 kg in crossbred Aberdeen Angus × Brahman (Huffman et al, 1990).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Rib eye area increased linearly as slaughter weight increased, which was similar to the results reported in the literature, in which increase in body weight at slaughter resulted in greater REA, both in late breeds, like Charolais (Restle et al, 1997); early breeds, like Aberdeen Angus (Costa et al, 2002b); crossings between various breeds (Cruz et al, 2004b); and Zebu breeds, like Gyr, Guzerat, Tabapuã and Nellore (Jorge et al, 1999). The rib eye area expressed in 100 kg cold carcass decreased with increase in body weight, agreeing with the results observed in the literature, demonstrating linear decrease from 27 to 24 and from 26.2 to 23.2 cm 2 /100 kg carcass, with increase in slaughter weight from 550 to 700, in crossbred Blonde D'Aquitaine × Charolais (Patterson et al, 1994) and from 440 to 507 kg in crossbred Aberdeen Angus × Brahman (Huffman et al, 1990).…”
Section: Resultssupporting
confidence: 89%
“…Costa et al (2002b) found decrease in the percentage of hindquarter in relation to carcass weight, with increase in slaughter weight from 340 to 370, 400 or 430 kg, also in accordance with the results found by Galvão et al (1991), who also observed reduction in the percentage of hindquarter with increased slaughter weight. However, Jorge et al (1999) did not find differences in the percentages of beef round with increase in slaughter weight from 500 to 550 kg for crossbred animals and from 450 to 500 kg for Nellore animals.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Segundo Jorge et al (2007) os animais Sindi são menores e mais leves que os da raça Guzerá, porém a raça possui circunferência torácica maior e esta variável permite que o animal possa aumentar seu consumo, embora não aumente seu desempenho. Esta afirmação justifica os dados apresentados neste trabalho, visto que o Sindi apresentou desempenho bem inferior ao do Guzerá, mas seu consumo em relação ao peso vivo foi superior.…”
Section: Resultsunclassified
“…Esta afirmação justifica os dados apresentados neste trabalho, visto que o Sindi apresentou desempenho bem inferior ao do Guzerá, mas seu consumo em relação ao peso vivo foi superior. Jorge et al (2007) citam que rações com baixo teor de volumoso ou que a qualidade deste tubo com menos teor de fibra, seriam mais indicadas para as condições tropicais, em função de um incremento calórico menor. Rações compostas exclusivamente de volumoso se traduzem em maiores temperaturas corporais e maiores frequências respiratórias em relação às rações ricas em concentrados, isto em virtude da elevação do metabolismo, para realizar a digestão; quando o animal consome alimento muito fibroso ele gera um incremento calórico maior, em função das atividades realizadas a nível de rúmem, o que o leva a diminuir a ingestão de alimentos resultando em menor quantidade de calor a ser dissipada, beneficiando o balanço energético entre o animal e o ambiente.…”
Section: Resultsunclassified